Role of Multidisciplinary Care in the Management of Hepatocellular Carcinoma - Byrd, Kia; Alqahtani, Saleh; Yopp, Adam C.; Singal, Amit G. (Seminars in Liver Disease, 2021)
Despite advances in treatment options for hepatocellular carcinoma (HCC), 5-year survival for HCC remains below 20%. This poor survival is multifactorial but is partly related to underuse of curative treatment in clinical practice. In light of growing treatment options, delivered by different types of providers, optimal management requires input from multiple specialties. A multidisciplinary approach has been evolving over the past couple of decades, bringing different specialists together to develop a therapeutic plan to treat and manage HCC, which significantly increases timely guideline-concordant treatment and improves overall survival. The present review attempts to highlight the need for such a multimodal approach by providing insights on its potential structure and impact on the various aspects of HCC management.
Keywords: liver cancer; treatment; multidisciplinary; guideline-concordant care; hepatocellular carcinoma